Optimal design of joint network LDPC codes over orthogonal multiple-access relay channels. (2016) - Wang, Jingyi; Che, Shuling; Li, Ying; Wang, Junlong
Optimisation of degree distribution for joint network LDPC code over orthogonal Multiple-Access Relay Channels (MARC) is investigated in this paper. We first use a differential evolution algorithm to optimise the degree distribution of the joint network LDPC code over orthogonal MARC based on Gaussian approximation. Then, using a modified differential evolution algorithm, we design a rate-compatible network LDPC code, which is equivalent to designing a single code with different Signal-to-Noise Ratio (SNR). Simulation results show that the gap between Bit Error Rate (BER) performance of the former algorithm and the decoding threshold is about 0.4 dB and that between the capacity limit and decoding threshold is less than 0.7 dB at BER = 10 −6 . Simultaneously, the gap between BER performance of the latter algorithm and the decoding threshold is about 0.52 dB and that between the capacity limit and the decoding threshold is less than 0.46 dB at BER = 10 −7 .